Raman microscopy investigation of beryllium materials. (12th January 2016) - Pardanaud, C; Rusu, M I; Giacometti, G; Martin, C; Addab, Y; Roubin, P; Lungu, C P; Porosnicu, C; Jepu, I; Dinca, P; Lungu, M; Pompilian, O G; et al.
Abstract: We report for the first time on the ability of Raman microscopy to give information on the structure and composition of Be related samples mimicking plasma facing materials that will be found in ITER. For that purpose, we investigate two types of material. First: Be, W, Be1 W9, and Be5 W5 deposits containing a few percents of D or N, and second: a Mo mirror exposed to plasma in the main JET chamber (in the framework of the first mirror test in JET with ITER-like wall). We performed atomic quantifications using ion beam analysis for the first samples. We also did atomic force microscopy. We found defect induced Raman bands in Be, Be1 W9, and Be5 W5 deposits. Molybdenum oxide has been identified showing an enhancement due to a resonance effect in the UV domain.